Send me down a miracle - Nolan, Han. (San Diego : Harcourt Brace & Co., 1996)
A sleepy, God-fearing southern town erupts in chaos when a flamboyant artist from New York City returns to her birthplace for an artistic experiment.
Keywords: Artists -- Fiction; Christian life -- Fiction